Goethe and the poets of Arabia - Mommsen, Katharina 1925- (Studies in German literature, linguistics, and culture, 2014)
Abundant evidence bears witness to Johann Wolfgang Goethe's lifelong predilection for the literature, religion, and culture of ancient Arabia. Scholars have hardly yet touched upon Goethe's relationship to Arabic literature. His remarkable West-östlicher Divan suggested that his interest in the "Orient" was limited to the Persian poet Hafez, his chief model for the collection, and to the culture of Persia. Yet significant aspects of this work and others stem from pre-Islamic and Islamic traditions of Arabian literature. This study examines comprehensively Goethe's relationship to Arabian culture, mediated primarily by his interest in certain poets and texts and by his highly nuanced attitude toward Muhammad, the Qur'an, and Islam. Katharina Mommsen has explored exhaustively Goethe's opinions about Arab poets and their sources, the numerous traces of Arabic poetry that entered his works, and the grounds for his ambivalent affinity for Islam and its Prophet. Extensive textual evidence reveals how throughout his life Goethe's temperament determined his interest in particular Arabian poets and was in turn modulated by them. The study also opens new perspectives on Goethe's biography, especially in the early nineteenth century when he was writing the Divan